HUBUNGAN KUALITAS HIDUP PASIEN HIPERTENSI DENGAN KARAKTERISTIK DEMOGRAFI MENGGUNAKAN INSTRUMEN EQ-5D DI PUSKESMAS S.PARMAN KOTA BANJARMASIN - Yumassik, Abdul Mahmud; Azizah, Nur; Illahi, Fitrah Shafran; Wahyuni, Amaliyah; Aisyah, Noor; Soraya, Soraya (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
This disease can affect the patient's quality of life if they do not receive appropriate therapy and risks causing complications which can worsen the patient's quality of life The research method used was observational with a cross sectional design. The population was hipertensive outpatient at the S. Parman Community Health Center for the period March 2023. The sampling technique used consecutive sampling technique to obtain a sample of 84 respondents. The research instrument uses the European Quality of Life 5 Dimensions (EQ5D). Data analysis used the EQ-5D index calculator and chi square test. The results showed that the distribution of respondents' characteristics included female gender (57.14%), age 56-65 (54.76%), high school education (50.00%), housewife occupation (34.52%), long suffering hypertension >5 years (60.71%), comorbidities (50.00%), no history of hypertension (52.38%), and hypertension category level 2 (53.57%). The percentage of good quality of life for hypertensive patients was 91.67%, while the poor quality of life for hypertensive patients was 8.33%. The variables of comorbidities (p-value=0.048) and hypertension category (p-value=0.010) have a significant relationship to the quality of life of hypertensive patients.